TANTANGAN IMPLEMENTASI PEMBAYARAN JASA LINGKUNGAN UNTUK PENCEGAHAN KONVERSI LAHAN PERTANIAN / The Challenges of Implementing Payment for Environmental Services to Prevent The Agricultural Land Conversion - Saridewi, Tri Ratna; Nazaruddin, Nazaruddin (Badan Penelitian dan Pengembangan Pertanian, 2021)
Payments for environmental services mechanism is expected to strengthen decisions of agricultural landowners to maintain the existence of their agricultural land. This mechanism is expected to prevent the conversion of land that occurs due to its lower appreciation compared to other uses. This study is aimed to critically examine the challenges of implementing payments for environmental services in Indonesia and strategies to improve the implementation of payments for environmental services schemes to reduce agricultural land conversion. Ostrom’s Institutional Analysis and Development framework is used to examine the implementation of Payments for environmental services. The implementation was able to run well through the establishment of institutions that regulate constitutional rules. The collaboration between the Government (as the user of environmental service) and farmers (as the service provider) should be declared and fully understood before the scheme is implemented. Therefore, full participation of all related parties was crucial in achieving the program’s goals. Collective understanding of the need to prevent land conversion and the coordination of stakeholders needs to be carried out sustainably.Keywords: Land, conversion, environmental services, paymentAbstrakMekanisme pembayaran jasa lingkungan diharapkan dapat memperkuat keputusan pemilik lahan pertanian untuk mempertahankannya. Mekanisme tersebut diharapkan dapat mencegah konversi lahan yang terjadi akibat apresiasi terhadap lahan pertanian secara ekonomi lebih rendah dibandingkan dengan penggunaan lainnya. Kajian ini bertujuan untuk menelaah secara kritis tantangan implementasi pembayaran jasa lingkungan di Indonesia dan strategi meningkatkan implementasi skema pembayaran jasa lingkungan untuk mengurangi konversi lahan pertanian. Kerangka Ostrom’s Institutional Analysis and Development digunakan untuk mengkaji implementasi pembayaran jasa lingkungan. Implementasi pembayaran jasa lingkungan dapat berjalan dengan baik melalui penetapan lembaga yang mengatur aturan konstitusional. Kontrak kerja sama antara pemerintah sebagai pengguna jasa lingkungan dengan petani sebagai penyedia jasa lingkungan harus disosialisasikan dan dipahami sebelum skema pembayaran jasa lingkungan dijalankan. Pelibatan partisipan secara penuh merupakan hal yang sangat penting dalam mencapai keberhasilan program. Pemahaman bersama tentang perlunya pencegahan konversi lahan dan koordinasi seluruh pemangku kepentingan terkait secara berkelanjutan sangat diperlukan.Kata kunci: Lahan, konversi, jasa lingkungan, pembayaran